ANALISIS STRATEGI PEMASARAN DIGITAL DALAM MENINGKATKAN PENJUALAN PT. MAYORA BEKASI - Prasetyaningsih, Nila; Ardiman, Dzaki (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to analyze the digital marketing strategy implemented by PT Mayora Bekasi in increasing sales of its products. In the ever-evolving digital era, companies are faced with the need to adopt innovative and effective marketing strategies to win the competition in the market. The research method used is a case study with a qualitative approach, where data is obtained through in-depth interviews with marketing managers, observation, and analysis of company documents.The results showed that PT Mayora Bekasi has implemented various digital marketing strategies such as the use of social media, search engine optimization (SEO), content marketing, and pay-per-click advertising. The use of social media such as Instagram, Facebook, and YouTube has proven effective in increasing consumer interaction and engagement. In addition, the right SEO strategy helps increase product visibility on search engines, making it easier for consumers to find the products offered. Informative and engaging content marketing also plays an important role in building brand awareness and consumer loyalty.However, this research also identified several challenges faced, such as intense competition in the digital world, changes in social media algorithms, and the need for constantly updated content. To overcome these challenges, PT Mayora Bekasi needs to continue to innovate and adapt to technological developments and dynamic market trends. Overall, this study concludes that an effective digital marketing strategy can significantly increase PT. Mayora Bekasi's sales. Recommendations include increased investment in digital marketing, training for the marketing team, and the use of data analytics to measure the effectiveness of the strategies implemented.